Acute Lower Leg Heating Increases Exercise Capacity in Patients With Peripheral Artery Disease. Issue 2 (March 2019) - Pellinger, Thomas K.; Neighbors, Catherine B.; Simmons, Grant H.
Abstract : Background/Objective: In this pilot study, we tested the hypothesis that acute lower leg heating (LLH) increases postheating popliteal artery blood flow and 6-minute walk distance in patients with peripheral artery disease (PAD). Methods: Six patients (5 male, 1 female) with PAD (69 ± 6.9 years; claudication: ankle-brachial index < 0.90) participated in 3 randomized treatment sessions (2–7 days apart): control or bilateral LLH conducted via water bath immersion (42°C; ~40-cm depth) for either 15 or 45 minutes. Popliteal artery blood flow (Doppler ultrasound) and arterial pressure were measured before and after LLH. Six-minute walk distance was measured on the control day and each experimental day 35 minutes post-LLH. Results: Popliteal artery blood flow increased after heating in a duration-dependent manner ( P < .05, postheating vs control for both heating conditions and between them). Six-minute walk distance increased by 10% and 12% after 15- and 45-minute heating treatments, respectively ( P < .05 vs control session). Conclusions: Lower leg heating, for as short as 15 minutes, increases postheating leg perfusion and exercise capacity in patients with PAD.